A novel ultra wideband circularly polarized stacked cylindrical dielectric resonator antenna with modified ground plane. Issue 8 (7th May 2022) - Patri, Upender; Kumar, Amarjit
Abstract: In this paper, two identical Cylindrical Dielectric Resonator Antennas (CDRA) are stacked together to achieve Circular Polarization (CP). Ultra wideband impedance bandwidth and wide axial ratio bandwidth is achieved by three factors: stacking of similar DRs, stepped conformal microstrip feed line which will generate orthogonal modes and new partial ground plane with circular rings. Measurement results show that the proposed stacked Cylindrical CPDRA achieves an Impedance Bandwidth (IBW) of ( S 11  < −10 dB) of 72.48% (3.65–7.8 GHz) and Axial Ratio Bandwidth (ARBW) (AR <3 dB) of 44.12% (4.38–6.86 GHz), respectively. In addition, the proposed antenna shows dominant Left Hand CP with gain ranges from 1.4 to 6.5 dBic with maximum radiation efficiency of 93.3%. The advantages and novel points of proposed research work is as follows: (i) The novel configuration of stacking CDRA's along with stepped microstrip feed enhances ARBW, (ii) New proposed partial ground plane with two circular rings provides enhancement in IBW, (iii) Simple design and small height of DRs produces enhanced IBW, ARBW, Gain and Efficiency. Furthermore, by changing the position of circular rings on ground plane, the proposed antenna provides dominant LHCP to RHCP conversion and achieves polarization reconfigurability. The proposed antenna configuration covers the frequency range of applications of C‐band and military satellite communication.